2014
DOI: 10.1111/imm.12175
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of new citrulline‐containing peptide epitopes by autoantibodies produced in vivo and in vitro by B cells of rheumatoid arthritis patients

Abstract: SummaryAnti-citrullinated peptide/protein antibodies (ACPAs) are highly sensitive and specific markers of rheumatoid arthritis (RA). Identification of peptide epitopes that may detect different subgroups of RA patients might have diagnostic and prognostic significance. We have investigated citrulline-and arginine-containing peptide pairs derived from filaggrin, collagen or vimentin, and compared this citrulline-peptide panel with the serological assays conventionally used to detect ACPAs. Furthermore, we studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 42 publications
0
32
0
5
Order By: Relevance
“…20,21 Ezen epitóprégión belül -az egészséges és RA betegségben szenvedõ személyek szérummintái-nak összehasonlításával -azonosítottuk azt a legkisebb peptidszakaszt ( 311 TXGRS 315 ), amely ellenanyag (B-sejt) epitópként viselkedik és alkalmas lehet a betegség korai és specifikus kimutatására. 123. évfolyam, 3. szám, 2017.…”
Section: áBraunclassified
“…20,21 Ezen epitóprégión belül -az egészséges és RA betegségben szenvedõ személyek szérummintái-nak összehasonlításával -azonosítottuk azt a legkisebb peptidszakaszt ( 311 TXGRS 315 ), amely ellenanyag (B-sejt) epitópként viselkedik és alkalmas lehet a betegség korai és specifikus kimutatására. 123. évfolyam, 3. szám, 2017.…”
Section: áBraunclassified
“…ACPAs can react with a variety of citrullinated proteins, such as vimentin, fibrinogen, a enolase, fillagrin, and type II collagen (3,4). Most clinical assays currently in use employ cyclic citrullinated peptides as the target Ag, which may lead to a small percentage of false-negative results (5,6).…”
Section: What Is Citrullination?mentioning
confidence: 99%
“…[26][27][28] We and others have previously shown that in vitro-activated B cells from ACPA-positive RA patients produce citrullinated peptide-specific IgG. 36,37 To see if XmAb5871 has an effect on citrulline peptide-specific antibody production, purified B cells from selected RA patients were cultured in the presence of IL-2 and R848 to stimulate memory B cells. The number of antibody-producing cells was estimated on citrulline-containing filaggrin-peptide coated plates.…”
Section: Ra B Cellsmentioning
confidence: 99%
“…37 Briefly, purified B cells from RA patient blood were isolated using MACS. 10 6 cells/ml were cultured in RPMI 1640 containing 10% FCS in the presence of 10 ng/ml rhIL-2 and 1 μg/ml R848 (Sigma-Aldrich, SML0196) polyclonal activator with or without XmAb5871.…”
Section: Peptide-specific Elispot Assaymentioning
confidence: 99%
See 1 more Smart Citation